A importância da administração de Beaurepaire Rohan no projeto urbano para a Parahyba - Gomes , Nayadson dos Santos (2016)
The emphasis of this research work is to analyze the importance of the administration of President Carlos Henrique Pedro Beaurepaire Rohan in the Province of Parahyba and its urban design for the city (1840-1859). For this purpose we will be using the cross section technique. This work will also be analysing the study of the city of Parahyba (João Pessoa in present days) during the historical period known as the Second Empire in the context to the administration of Beaurepaire Rohan and the comparison with other urban administrations of the Second Empire. There will be a characterization of the works of Beaurepaire Rohan to the city of Parahyba.